Hidden in the plain sight: a new species of Rhabdophis (Serpentes: Natricinae) from the Rhabdophis himalayanus complex - Das, Abhijit; Smith, Eric N.; Sidik, Irvan; Sarker, Goutam C.; Boruah, Bitupan; Patel, Naitik G.; Murthy, B.h.c.k; Deepak, V. (Zootaxa, 2021)
A new species of natricine snake of the genus Rhabdophis is described from Northeast India. Morphologically the new species is similar to Rhabdophis himalayanus but it can be distinguished from it by lacking a nuchal groove and nuchal glands, being relatively smaller, and having a distinct neck, ventral, and subcaudal coloration. In overall coloration it resembles R. chrysargos, from which it is distinguished by several aspects of its morphology and genetic differences. The discovery of Rhabdophis bindi sp. nov. reveals that forested regions in the northeastern part of India needs further biological exploration.